Mallorca: biser ali madež v Sredozemlju? - Potočnik Slavič, Irma (Geografski obzornik, 2000)
Due to beneficial conditions (i.e. Mediterranean climate, low prices, charter flights, interesting landscape, influence of fashion etc.) Balearic Islands represent a testcaseof mass charter tourism. Only several regions (mountainousedge, central part) are "unspoiled" in tourist sense. The third part represent very expensive and exclusive places occupied by international jet set. Articel focuses on factors which have influenced the development of tourism, and on different positive and negative effects of tourism on Mallorca.
Keywords: Baleari; družbena geografija; Mallorca; Španija; turistična geografija; turizem